FRI0072 DISCONTINUATION OF DMARD USE IN RHEUMATOID ARTHRITIS PATIENTS WITH LUNG DISEASE. (2nd June 2020) - Pedro, S.; Mikuls, T.; Zhuo, J.; Michaud, K.
Abstract : Background: Pulmonary manifestations such as interstitial lung disease (ILD) and chronic obstructive pulmonary disease (COPD) are frequent extra-articular features that carry a poor prognosis in Rheumatoid Arthritis (RA). Little data is available on how RA patients (pts) with pulmonary disease are managed in real-world settings. Objectives: To assess treatment patterns and DMARD discontinuation in RA patients with comorbid lung disease in comparison with other RA patients. Methods: The study included RA Patients enrolled in the Forward Databank with ≥1 year observation after 2000 initiating a DMARD. Forward is a large longitudinal rheumatic disease registry in the US. RA patients' diagnoses were rheumatologist-confirmed, and every 6 months participants completed comprehensive questionnaires regarding symptoms, disease outcomes, medications, and clinical events. Lung disease (LD+) was defined as at least one of the following: emphysema, asthma, bronchitis, COPD, pleural effusion, fibrosis of the lung, "RA lung", or ILD, the later classified by ICD9 codes (England 2019). DMARDs were categorized hierarchically into four groups: csDMARDs, TNFi and NTNFi (bDMARDs), and tsDMARDs. Percentage of patients who initiated different DMARDs were reported for pts with LD+/LD-. Discontinuation was analyzed by Kaplan Meier (KM) curves, log-ranks tests, and Cox regression models using time-varying covariates. Best models were created using backward selection models (10% probability of removal) and pre-defined clinical models. Results: Of the 21, 525 eligible RA patients, 13.8% had LD+ at the time they initiated a DMARD (follow-up: 69, 597 pt-yrs (median 1.9 yrs/pt)). LD+ patients tended to have more severe RA outcomes and comorbidities. MTX-monotherapy (48% vs 44%, p<0.001) and NTNFi were initiated more frequently in LD+ pts with lower use of TNFi (Figure). DMARD discontinuation rates were higher among LD+ patients for all DMARD groups, but KM curves were only significantly different for csDMARDs and TNFi. Different HRs for LD+ were found depending on the model used ranging from 1.18 to 1.28, and all models revealed an increased risk of discontinuation for LD+ patients. Compared to csDMARDs, TNFi were more often discontinued (Table). Other variables associated with an increased risk of discontinuation included: HAQ, Rheumatoid Disease (RD) comorbidity index, pain, prior bDMARDs, and csDMARDs. Conclusion: Different DMARD treatment patterns were found for LD+ patients, who tended to initiate more csDMARD and NTNFi and less likely to initiate a TNFi. LD+ patients were at a higher risk of discontinuation irrespectively of the DMARD treatment, but with greater risk for TNF users. References: [1]England BR, et al. Arth Care Res. doi:10.1002/acr.24043. Disclosure of Interests: Sofia Pedro: None declared, Ted Mikuls Grant/research support from: Horizon Therapeutics, BMS, Consultant of: Pfizer, Joe Zhuo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Kaleb Michaud: None declared